PELAKSANAAN KOORDINASI PENERTIBAN PEDAGANG KAKI LIMA PADA BIDANG OPERASIONAL DAN KETERTIBAN UMUM - Ikhsan E.2111055 (FISIP Universitas Tanjungpura, 2014)
The aims of this article is intended to provide an understanding of the functional coordination in implementation of the control of street vendors (PKL) in the River Market District of New Trench Kingdom. The phenomenon that occurs on the implementation of coordination in regulating street vendors conducted Civil Service Police Unit in the District of Sungai Raya in fact a lack of support from relevant agencies, so there is still a lot of the street vendors who sell in places that violate the city's zoning requirements, such as disturbing the beauty of the city, road traffic is getting narrower. That is because the lack of understanding of the rules of order and hold a street vendor environment. The results showed that the implementation of functional coordination in the control of street vendors in New Market River District Ditch the Kingdom had not been effective. This can be seen from several indicators, among others: implementation of coordination through coordination meetings, request data or information regarding the vendors, the consultation exercise and a relationship of cooperation between States through the Civil Service Police Unit with relevant agencies and groups of street vendors have not run up, because not formal and informal relations, such as, rarely do meetings or deliberations of work, always feel the most important duties and the absence of regulation of business groups on a regular basis. With such circumstances misunderstandings always happen, and sometimes act often throwing the responsibility ultimately any decision made less precise, especially in penetaan street vendors.Keywords: Coordination, curbing, street vendors